Faktor-Faktor Yang Mempengaruhi Perilaku Tidak Memilih Pada Pemungutan Suara Ulang (PSU) DPD Provinsi Sumatera Barat Di Kota Bukittinggi Tahun 2024 - Bagas Islam Mahendra (Faculty of Social and Political Sciences, Universitas Singaperbangsa Karawang, Indonesia, 2025)
This study aims to analyze the factors influencing non-voting behavior in the Re-voting Process (Pemungutan Suara Ulang/PSU) for the Regional Representative Council (DPD) election in West Sumatra Province in 2024, specifically in the city of Bukittinggi. Bukittinggi recorded the lowest voter turnout in West Sumatra during the PSU, with participation reaching only 26%. This research employs a quantitative approach using an explanatory survey method. Data were collected through questionnaires administered to 100 respondents selected using a multistage random sampling technique. The theoretical framework applied is the Civic Voluntarism Model proposed by Sidney Verba, which includes variables of resources, psychological engagement, and recruitment (mobilization). Data analysis was conducted using multiple linear regression with the assistance of SPSS version 26. The findings indicate that non-voting behavior is significantly influenced by internal individual factors, namely resources and psychological engagement. A paradoxical relationship was identified in the resource variable, where higher levels of resources are associated with a greater tendency toward non-voting behavior due to time constraints and occupational commitments. Conversely, external factors such as recruitment or mobilization were found to have no significant effect on individuals’ decisions not to vote. Keywords: Non-Voting Behavior, Civic Voluntarism Model, Re-voting, Political Participation